2023
DOI: 10.1002/ijgo.15152
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of menstrual disorders and their association with psychological stress in Syrian students enrolled at health‐related schools: A cross‐sectional study

Fares Kahal,
Sarah Alshayeb,
André Torbey
et al.

Abstract: ObjectivesMenstrual disorders are among the most prevalent health issues among young female students studying in health science faculties. This study aimed to provide insights into the menstrual patterns among medical faculty students and determine whether stress can be a risk factor for its various disorders.MethodsThis cross‐sectional study was conducted in the Faculties of Medicine, Dentistry, and Pharmacy at the Syrian Private University, Damascus, Syria, between October and November 2022. A total of 980 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(105 reference statements)
1
0
0
Order By: Relevance
“…Regarding the associated factors, in the current study, we found a correlation between overall stress and different types of stress and menstrual symptoms in both the pre-and intra-menstrual phases. These findings support the premise that stress is associated with menstrual distress, which has been reported in a previous systematic review of medical students [24] and in Japan [25,26], among students in Korea [27,28], among international students in China [29], and among Syrian students [30]. A study conducted among college students in Nigeria revealed that those who experienced academic stress were approximately twice as likely to develop menstrual disorders [31].…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the associated factors, in the current study, we found a correlation between overall stress and different types of stress and menstrual symptoms in both the pre-and intra-menstrual phases. These findings support the premise that stress is associated with menstrual distress, which has been reported in a previous systematic review of medical students [24] and in Japan [25,26], among students in Korea [27,28], among international students in China [29], and among Syrian students [30]. A study conducted among college students in Nigeria revealed that those who experienced academic stress were approximately twice as likely to develop menstrual disorders [31].…”
Section: Discussionsupporting
confidence: 88%